Monitoring the in-situ oxide growth on uranium by x-ray photoelectron spectroscopy. (20th September 2019) - Sun, Chaolun; Pan, Qifa; Zhong, Huoping; Hu, Yin; Luo, Lizhu; Wang, Xiaofang; Liu, Kezhao
Abstract: In the present work, we report the in situ monitoring of oxide growth on metallic uranium surface at room temperature for oxygen pressures from 1 × 10 −7 to 5 × 10 −7 Pa by means of x-ray photoelectron spectroscopy. The oxidation products were analyzed briefly and a quantitative relationship between the oxide film thickness and oxidation time was established and the rate constant was obtained. Results show that the sub-stoichiometric uranium oxides (UO2−x ) were formed, and further transformed to those with smaller x values. We found that oxygen pressure has a positive effect on the rate constant as well as the oxide film thickness, and instead of oxygen pressure, oxygen exposure has a vital impact on determination of the thickness of the oxide layer.